2017
DOI: 10.1097/mph.0000000000000797
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Oral Vitamin D and Calcium Supplementation With Bone Mineral Density in Pediatric Acute Lymphoblastic Leukemia Patients

Abstract: Vit D and Ca supplementation in pediatric ALL patients during intensive chemotherapy may not prevent bone mineral loss. BMD scores of pediatric ALL patients described by other studies, as a major decrease in the first 2 years and gradual increase afterward, was also observed in our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
0
15
1
2
Order By: Relevance
“…Gunes, et al [9] reported that low calcium and vitamin D intake could have provided to an abnormal bone mineralization in patients undergoing treatment of ALL and they recommend prophylactic vitamin D to patients in the first two years of treatment which was found the most critical period for BMD decrease [9]. In contrast with this study, Diaz, et al [10] and Demirsoy, et al [11] reports found that there was not any significant between the calcium-vitamin D supplementation and BMD.…”
Section: Discussioncontrasting
confidence: 54%
“…Gunes, et al [9] reported that low calcium and vitamin D intake could have provided to an abnormal bone mineralization in patients undergoing treatment of ALL and they recommend prophylactic vitamin D to patients in the first two years of treatment which was found the most critical period for BMD decrease [9]. In contrast with this study, Diaz, et al [10] and Demirsoy, et al [11] reports found that there was not any significant between the calcium-vitamin D supplementation and BMD.…”
Section: Discussioncontrasting
confidence: 54%
“…Studies of vitamin D/calcium supplementation in children with juvenile rheumatoid arthritis or idiopathic juvenile osteoporosis have shown improvement in BMD and a decreased fracture rate . Some retrospective studies in survivors have shown higher BMD in patients taking vitamin D/calcium supplements, but a randomized trial showed no difference in mean BMD change between survivors assigned to vitamin D/calcium supplementation versus placebo . Further studies are needed to inform interventions for survivors with reduced BMD.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized double-blind study showed that nutritional counseling and vitamin D and calcium supplementation for 2 years offered no benefit for improving BMD among adolescent and young adult survivors of ALL [46]. Recently, a similar result was reported from a Turkish study group [47]. Depending on these findings, alternative and more aggressive strategies are needed to prevent these patients from experiencing bone complications.…”
Section: Discussionmentioning
confidence: 85%